Improving thin bed identification in Sarawak Basin Field using short time fourier transform half cepstrum (STFTHC) methos - M Nizarul, M. Hermana, Yasir Bashir, Deva Ghosh, . (2015)
In delineating complex subsurface geological feature, broad band of frequencies are needed to unveil the often hidden features of hydrocarbon basin such as thin bedding. The ability to resolve thin geological horizon on seismic data is recognized to be a fundamental importance for hydrocarbon exploration, seismic interpretation and reserve prediction.